112 Cerebral venous sinus thrombosis: a large retrospective audit from a regional neurosciences centre. Issue 6 (27th May 2022) - Batcheller, Lisa; Appleton, Jason P; Hayton, Tom
Abstract : Introduction: Cerebral venous sinus thrombosis (CVST) can be a challenging condition to diagnose and treat. We previously performed an audit of CVST patients (2010–2014) and sought to re-audit for changes in practice. Methods: We performed a retrospective audit of CVST patients admitted to Queen Elizabeth Hospital Birmingham, auditing against international guidelines. Comparisons with 2010–2014 data used Fisher's exact test. Results: Between June 2015 and June 2019, 88 patients with CVST were included. Median age 44 years (range 16–87), 56% female. 56 (64%) patients underwent CT venography (CTV) and 16 (18%) MR venog- raphy (MRV); a greater proportion underwent venography than in 2010–2014 (31/51, 61%, p<0.001). Low molecular weight heparin was the commonest initial anticoagulant: 2010–2014 68% vs. 2015–2019 73% (p=0.70). There was a tendency towards less IV heparin over time: 18% vs. 7% (p=0.09). Although warfarin was the most common long-term anticoagulant in both audit periods (69% vs. 43%), direct oral antico- agulants (DOACs) were used in 12 (14%) patients in 2015–2019. 53% had thrombophilia screening despite this not being routinely recommended. Conclusions: In 2015–2019, a greater proportion of patients with CVST were diagnosed using CTV/MRV and received less IV heparin. DOAC usage is increasing in CVST. Thrombophilia screening remains controversial. lisabatch1@gmail.com